Efficiency of parallel programming in the Open MP Standard - Gapbarova, Perizat (MMIT Proceedings, 2024)
The purpose of the study is to identify the features of performing computing in a parallel computing environment. In accordance with the goal, the task was set: to identify the features of performing computing in the OpenMP environment (a standard for parallel computing); to study the effectiveness of actions performed in OpenMP; and to experimentally describe the practical implementation of didactic principles. The article presents, from the author’s point of view, a brief description of the methods of obtaining knowledge and achieving success based on parallel programming and parallel data processing using computer tools. Solving simple problems of the numerical method by parallel computing can include many methods and techniques. The fact that various libraries and structures can be used in the OpenMP standardization environment to solve specific tasks is demonstrated using the experimet tasks[1]. Thus, it is argued that the rapid development of the modern information technology industry is inextricably linked with the training of experienced, modern specialists in the field of high-performance computing. As a result of the study, it was found that parallel computing of simple tasks for any users gives them a significant opportunity to perform efficient computing.